Targeting USP42 induces DNA damage and inhibits cell growth in prostate cancer - Zhou, Yinghao; Chen, Chenchen; Meng, Yibo; Ge, Jianchao; Meng, Shengkui; Wang, Xillong; Xu, Yaozong; Shi, Guowei; Yu, Wandong; Hu, Xuetao; Zhang, Jun (Frontiers in Molecular Biosciences, 2025)
BackgroundProstate cancer (PCa) is one of the most common cancers in men worldwide. During its progression, deubiquitination-mediated alterations in biological processes play critical roles in tumor metabolism, stem cell characteristics, immune evasion, DNA damage repair, and chemoresistance. A comprehensive investigation of the deubiquitinases involved in PCa development holds significant clinical value as regards inhibiting tumor growth and overcoming drug resistance.MethodsClinical databases were analyzed to identify differentially expressed deubiquitinases in PCa. Immunohistochemical analysis of PCa samples was used to evaluate USP42 expression in normal and tumor tissues. The effects of USP42 inhibition on PCa cell proliferation were assessed both in vitro and in vivo through MTT assays, colony-formation assays, and a subcutaneous xenograft tumor model in nude mice. The regulation of USP42 expression by the androgen receptor (AR) was investigated by culturing cells in low-androgen medium, modulating AR expression, and analyzing protein expression correlations through immunohistochemical staining of clinical samples and database analysis. The potential mechanisms underlying USP42-mediated effects on PCa cell proliferation were explored using RNA sequencing and data-independent acquisition proteomics. In addition, γ-H2A.X detection, MTT assays, and colony-formation assays were conducted to evaluate the impacts of USP42 inhibition on DNA damage repair and the therapeutic efficacy of olaparib in PCa cells.ResultsKnockdown of USP42 significantly reduced PCa cell growth both in vitro and in vivo. USP42 expression was elevated in PCa tissues compared with normal tissues. Further investigation confirmed that AR positively regulated USP42 mRNA and protein expression in PCa cells. Mechanistically, USP42 inhibition induced significant defects in DNA damage repair. Moreover, USP42 knockdown markedly enhanced the tumor-suppressive effects of olaparib when used in combination.